2004
DOI: 10.1021/jp0372789
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Pathways in a Series of CH3COX Molecules in the Strong Field Regime

Abstract: In intense laser fields, fragment ions can be produced from CH 3 COX (X ) CH 3 , CF 3 , and C 6 H 5 ) either by absorption and dissociation followed by ionization (ADI) or absorption and ionization followed by dissociation (AID). Electronic structure calculations were carried out using Hartree-Fock, density functional, and correlated levels of theory to understand the possible fragmentation pathways. The calculated ionization potentials are in very good agreement with the available experimental data. For aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Paltenghi et al 25 have suggested that the reactivity of alkyl radicals with Cl 2 is determined largely by long‐range attractive forces, and a correlation of the rate coefficient for barrierless reactions with the reactant molecules ionization potential (IP) has been proposed. The IP values for HCO 26 and CF 3 CO 27 are 8.6 eV and that for CH 3 CO is 7 eV 26. Hence, the rate coefficient for the Cl 2 + CH 3 CO reaction is expected to be greater than the analogous HCO and CF 3 CO reactions.…”
Section: Discussionmentioning
confidence: 91%
“…Paltenghi et al 25 have suggested that the reactivity of alkyl radicals with Cl 2 is determined largely by long‐range attractive forces, and a correlation of the rate coefficient for barrierless reactions with the reactant molecules ionization potential (IP) has been proposed. The IP values for HCO 26 and CF 3 CO 27 are 8.6 eV and that for CH 3 CO is 7 eV 26. Hence, the rate coefficient for the Cl 2 + CH 3 CO reaction is expected to be greater than the analogous HCO and CF 3 CO reactions.…”
Section: Discussionmentioning
confidence: 91%
“…The other radical cleavage products, phenyl and acetyl radicals, are also observed but with a much lower yield. 45,52,53 Like benzaldehyde, the yield of chemical products is seen to approach unity with S 2 excitation at the lowest pressures but decreases coincident with increasing phosphorescence when foreign gas is added, suggesting a vibrationally excited intermediate to fragmentation. Only trace amounts of the molecular dissociation products of carbon monoxide and toluene were detected after photolysis by 193 and 248 nm radiations; a branching ratio with the radical products of ϳ1 : 100.…”
Section: B Acetophenonementioning
confidence: 99%
“…[11][12][13] Both molecules have been observed to dissociate upon UV irradiation: benzaldehyde along a molecular dissociation pathway leading to closed-shell species, benzene and carbon monoxide, [14][15][16][17][18][19][20][21] and acetophenone into radical products, benzoyl and methyl radicals. 16,[22][23][24] Minor radical production pathways have also been detected from benzaldehyde. 25,26 In the condensed phase, photophysical studies of benzaldehyde 5 and acetophenone 6 ͑in matrices͒ and benzaldehyde derivatives 27 ͑in solution͒ indicate that the triplet ͑T 2 ͒ state becomes the lowest in energy and hence identifiable by its emission.…”
Section: Introductionmentioning
confidence: 99%